Shaping Perceptions: The Taliban’s Use of Digital Media for Public Diplomacy and Image Building After Seizing Power in Afghanistan - Fitry Wahyuni; Hasbi Aswar (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
After 20 years of fighting against the invasion of the United States and its allies, the Taliban succeeded in taking power in Afghanistan on August 15, 2021. The return of the Taliban to power caused much controversy, especially regarding human rights. The Taliban tried to improve their negative image by increasing soft power through public diplomacy and utilizing digital media to strengthen their messages to the public. This study aims to analyze how the Taliban conducts public diplomacy through digital media to build a positive image after the takeover of power in Afghanistan. The method used was qualitative, using literature through online searches, especially digital media owned by the Taliban. This research found that the Taliban actively engages in public diplomacy by using digital media such as websites, YouTube, and Twitter to respond to narrative attacks and promote policies to build a positive image.